Depression, the internet and ethnography : a study of online support forums and the methodology used : a thesis presented in partial fulfilment of the requirements for a Master of Arts degree in Social Anthropology at Massey University, Albany Campus - Hawkey, Michael Andrew (Massey University, 2005)
Depression is one of the more common forms of mental illness experienced by people around the world. It is an illness which affects both men and women alike and does not target specific ages or nationalities. Depression is also an illness many suffer in solitude, often unable to pinpoint what exactly is wrong, rather identifying it as a “darkness” or sense of “numbness”. As we move into an age of growing technological changes, the Internet has become host to many forms of communities. These communities can be both modified versions of their offline original or whole new communities that did not exist to any great degree before the introduction of the internet. One such new form of online community are those designed for the support of peoples with depression and other mood disorders. Because of this growth in online communities and anthropology’s tradition of researching and understanding different groups of people, it is only appropriate that, as a discipline, it also moves online alongside these new communities. To do this, traditional field methods need to be reassessed and new potential problems and ethical dilemmas resolved. As online depression communities and internet ethnography are both relatively new fields of study, this thesis will examine the elements of both the online depression communities being studied, and the methods used in researching them. The reason I chose to research this topic is because, although depression as a subject has been covered many times before, and online community research is growing, there have been few studies undertaken on the two combined. In undertaking such research, this study will be of use for both academia and the public mental health sector. Academically, it provides us with an additional study venturing into online iii research and how to apply our tools within it. For the mental health sector, it provides an account as to how and why people with mental health issues deal with their problems, or at least begin to deal with them. This is important, as in the mental health sector many people with a mental illness may not reach out for help until in dire need. With the growth of online communities people may join earlier in their suffering and this knowledge could be of use for departments of mental health.
Keywords: Depression; Mental illness; Mental health; Internet; Online communities; Fields of Research::370000 Studies in Human Society::370300 Anthropology::370302 Social and cultural anthropology